A systematic examination of the nature and content of vignettes in schizophrenia research. (3rd May 2016) - Aldersey, Heather M.; Huynh, Doan Chinh; Whitley, Rob
Abstract: Background : Vignettes are often used in psychiatric research, yet there are few systematic studies on their content, creation, and use. Aims : This article describes a study of: (a) how researchers create vignettes in research on schizophrenia and (b) how these vignettes portray individuals with schizophrenia. Method : We conducted a systematic search of the PubMed database for articles between 2008 and 2012 that used vignettes to measure attitudes about schizophrenia. We analyzed the identified vignettes using a tool developed in reference to DSM criteria. Results : Within the vignettes, 98% of individuals portrayed demonstrated delusions, 91% demonstrated hallucinations and 29% demonstrated disorganized speech. The majority of vignettes portrayed individuals under 25 years and when both genders were not depicted, researchers chose to depict men much more frequently than women (41% vs. 8%). A majority of articles did not use original vignettes (55%), and many of the articles (53%) contained vignettes created by one team of researchers. Most vignettes did not include positive language or recovery-oriented information. Conclusions : This study highlights a need for critical thought on vignette development and utilization, especially as psychiatry is now moving towards a recovery-based understanding of mental illness.